Dynamic Routing Framework for Wireless Sensor Networks - Venkataraman, Mukundan; Chatterjee, Mainak; Kwiat, Kevin (IntechOpen, 2010)
Numerous routing protocols have been proposed for wireless sensor networks. Each such protocol carries with it a set of assumptions about the trafï¬c type that it caters to, and hence has limited interoperability. Also, most protocols are validated over workloads which only form a fraction of an actual deploymentâ€™s requirement. Most real world and commercial deployments, however, would generate multiple trafï¬c types simultaneously throughout the lifetime of the network. For example, most deployments would want all of the following to happen concurrently from the network: periodic reliable sense and disseminate, real time streams, patched updates, network reprogramming, query-response dialogs, mission critical alerts and so on. Naturally, no one routing protocol can completely cater to all of a deployments requirements. This chapter presents a routing framework that captures the communication intent of an application by using just three bits. The traditional routing layer is replaced with a collection of routing components that can cater to various communication patterns. The framework dynamically switches routing component for every packet in question. Data structure requirements of component protocols are regularized, and core protocol features are distilled to build a highly composable collection of routing modules. This creates a framework for developing, testing, integrating, and validating protocols that are highly portable from one deployment to another. Communication patterns can be easily described to lower layer protocols using this framework. One such real world application scenario is also investigated: that of predictive maintenance (PdM). The requirements of a large scale PdM are used to generate a fairly complete and realistic trafï¬c workload to drive an evaluation of such a framework.